Orchestrating Technology with Suggestopedia Method and Mind Mapping Technique in Teaching Reading - Meilany Mutiara Putri; Nia Kurniawati; Halimah (SEAMEO QITEP in Language, 2022)
Reading is one of the language skills that are important to be developed by students because they can get a lot of information they need to support their studies. The students can face difficulties in understanding the content and the purpose of several types of reading text if they do not have a good ability to comprehend the text. One of the reading text types is narrative text. Students faced some difficulties in comprehending narrative text, such as finding the generic structure of a story and other elements. This study aimed to investigate the orchestrating technology with the suggestopedia method and mind mapping technique in teaching reading narrative text. The subject were students of Bhakti Medika Health Vocational School Cianjur from 10 FKK, which involved 15 students. This study used a descriptive qualitative method, employing classroom observation and an open-ended questionnaire to gather the data. Based on the result of the observation, Suggestopedia method was implemented in three meetings. There were six stages implemented by the teacher in each meeting. Over the observation, it was also can be recorded that the implementation of suggestopedia method and mind mapping technique promoted the students’ behavioral engagement where the student paid attention, they were active and focus. The students also showed enthusiasm, which involved emotional engagement. Furthermore, the students could work well in the group and understand the material, which made students master narrative text. It was also suitable for students with audiovisual learning styles.